Welfare State Retrenchment - The Case of Japan - Takao, Yasuo (Cambridge University Press, 1999)
The purpose of this article is to examine the implications for welfare state retrenchment of central-local financial relations. In the post-war period, welfare state expansion has been a dominant theme in the development of central-local government relations in advanced industrial democracies. By the 1980s, however, nearly all OECD member countries had resorted to deficit financing as stagnant tax revenues combined with political pressure for increased public services. Faced with the urgent necessity of fiscal reconstruction, conservatives in advanced industrial democracies have favoured cutting public services throughout the 1990s. As always in times of retrenchment, elected officials have needed to win the goodwill of voters and interest groups for these unpopular cutbacks. There is no doubt that the politics of retrenchment is distinctively different from that of growth. Despite this new stage in the development of the welfare state, few systematic attempts have been made to analyse the impact of retrenchment politics on central-local financial arrangements. This article contributes to the new debate on comparative theories of retrenchment by analysing the impact of welfare state retrenchment in the context of Japan's recent fiscal reconstruction.